RESPON PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) TERHADAP APLIKASI PUPUK N-P-K (12-0,6-6) - Nasamsir Nasamsir (Universitas Batanghari, 2016)
AbstractThis research aims to know the oil palm seedling growth response in the main nursery toward N-P-K (12-0,6-6) fertilizer with the trademark Vedagro with different doses. The research was carried out in the Paal Merah Lama village, Southern Jambi sub district, started from 16 September until 16 Desember 2015. The research design used was Completely Randomized Design, with fertilizer dose of Vedagro as a treatment which consists of 6 levels, namely: d0 (control), d1 (5 g polybag-1), d2 (10 g polybag-1), d3 (15 g polybag-1), d4 (20 g polybag-1) and d5 (25 g polybag-1), using 4 replicates. The observed variables a plant height, totally plant leaf area, plant dry weight, and shoot-root ratio. The material used is oil palm seedlings aged 3 mounths. Data were analyzed using analysis of varians, then continued by Duncan test (DNMRT) at the 5% level. The results showed that giving real effect against the Vedagro fertilizer to plant height, totally plant leaf area, plant dry weight, and shoot-root ratio. 20 g dose of Vedagro fertilizer, showed the best effect on seeds height and dry weight, while the best effect on shoot-root ratio and totally plant leaf area was in 15 g dose.Keywords; the growth of plants, fertilizer application AbstrakPenelitian ini bertujuan untuk mengetahui respon pertumbuhan bibit kelapa sawit di pembibitan utama terhadap pemberian pupuk N-P-K (12-0,6-6) (merek dagang Vedagro) dengan dosis yang berbeda. Penelitian dilaksanakan di kelurahan Paal Merah Lama kecamatan Jambi Selatan, mulai 16 September sampai 16 Desember 2015. Rancangan yang digunakan adalah Rancangan Acak Lengkap (RAL), yaitu dosis pupuk Vedagro yang terdiri dari 6 level yaitu, d0 (kontrol), d1 (5 g polybag-1), d2 (10 g polybag-1), d3 (15 g polybag-1), d4 (20 g polybag-1) dan d5 (25 g polybag-1), dengan 4 ulangan. Peubah yang diamati adalah tinggi tanaman, luas daun total, berat kering tanaman dan nisbah tajuk akar. Bahan yang digunakan adalah bibit kelapa sawit berumur 3 bulan. Analisis data menggunakan analisis ragam dan dilanjutkan dengan uji Duncan (DNMRT) pada taraf α 5 %. Hasil penelitian menunjukkan bahwa pemberian pupuk Vedagro berpengaruh nyata terhadap tinggi bibit, luas daun total, berat kering tanaman dan nisbah tajuk akar. Pemberian pupuk Vedagro dengan dosis 20 g polybag-1 memperlihatkan pengaruh terbaik terhadap tinggi bibit dan berat kering bibit, sedangkan dosis 15 g polybag-1 menghasilkan pengaruh terbaik pada nisbah tajuk akar dan luas daun total. Kata kunci ; pertumbuhan tanaman, aplikasi pupuk